Estimation of Stature from Length of Middle Finger using Regression Analysis among Adults in Visakhapatnam, Andhra Pradesh: A CrossSectional Study - B.V.S. Anand Rao; Raja Sekhar Uppu; Govindaraju S.L. Manojna (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Stature estimation is a crucial element of forensic identi𿿿cation, speci𿿿cally in cases involving mass disasters and unknown bodies. Establishingreliable associations between body measurements and height is essential for accurate identi𿿿cation. Aim: To assess the association between middle𿿿nger length and height among dults in Visakhapatnam, Andhra Pradesh Materials and Methods: Cross-sectional research was carried out with 147 subjects (75 males and 72 females) aged 21 years and above, ensuring completion of skeletal growth with fused secondary ossi𿿿cation centres. The mean age was 26.82 years. Stature was recorded in centimetres, and middle 𿿿nger lengths (right and lft) were recorded. Results: The mean height of subjects was 162.04 ± 8.51 cm. The mean right and left middle𿿿nger lengths were 7.44 cm and 7.3 cm, respectively. A noable association w found between middle𿿿nger length and height for both hands (p < 0001). The right middle𿿿nger showed a slightly stronger predictive value than the eft. Conclusion: Middle 𿿿nger length serves as a notable and reliable predictor of height. Both right and left middle 𿿿ngers can be effectively used for heghtestimation, making this approach valuable in forensic cases where only partial remains are available.